DESAIN DAN IMPLEMENTASI INTERLEAVED BOOST CONVERTER UNTUK POWER FACTOR CORRECTION MENGGUNAKAN PENGENDALI LOGIKA FUZZY - Mentari Putri Jati; Era Purwanto; Bambang Sumantri; Sutedjo Sutedjo; Dimas Okky Anggriawan (Politeknik Negeri Batam, 2020)
In recent years there is an increasing demand for closely regulated dc power supply. Most of the power electronic converters in these power supplies used full wave rectifier. Bulky filter capacitor in rectifier can effect non-sinusoidal input current waveform (distorted). The difference in voltage and current waveform affected the power factor system. Interleaved Boost Converter (IBC) as Power Factor Correction (PFC) with a fuzzy logic controller to be added in the system to achieved near to unity power factor. IBC operated in Discontinuous Conduction Mode (DCM). Power factor near to unity can be achieved while rectifier supplied resistive load, the waveform of load current through back to input source have the same form with the input voltage. Simulation and hardware implementation is used by varying loads. The experimental results with a variable load value of IBC as PFC can improve the power factor system from 0.67 to 0.93.